SUN-238 Clinical Presentation, Management And Follow-up Of 83 Leydig Cell Tumors Of The Testis: A Prospective Case-cohort Study. - Isidori, Andrea (J Endocr Soc, 2019)
CONTEXT: Increasing referrals for testicular imaging have led to an increase in findings of Leydig cell tumors (LCTs). Their features and natural history remain largely unknown, as they were previously treated aggressively and were not followed up, and the available studies are small and heterogeneous. SUBJECTS AND METHODS: Case-cohort study of consecutive patients diagnosed with LCTs prospectively enrolled from 2009 to 2018, and matched cohorts of patients with seminomas or no testicular lesions (NoL) screened in the same timeframe. RESULTS: Over ten years, 83 patients were diagnosed with LCTs and compared against 90 seminoma patients and 2683 patients without testicular lesions (NoL). LCTs were diagnosed by enucleation (48.2%), orchiectomy (13.3%) or clinical surveillance (38.5%). Testicular volume (p=0.001), sperm concentration (p=0.001) and morphology (p<0.001) were lower in LCTs than in NoL. FSH, LH and SHBG were higher and the testosterone/LH ratio lower in LCTs (p<0.001). LCTs showed higher SHBG (p=0.018) and lower sperm concentration (p=0.029) motility (p=0.049) than seminomas. Risk factors for LCT were cryptorchidism (χ2 =28.27, p<0.001), gynecomastia (χ2=54.22, p<0.001) and low testicular volume (χ2= 11.13, p=0.001). Five cases were recurrences or bilateral lesions; none developed metastases during follow-up (median 66 months). CONCLUSIONS: LCTs have a good oncological prognosis when recognized early, as tissue-sparing enucleation is curative and should replace orchiectomy. However, infertility, gynecomastia, low testicular volume and cryptorchidism are common, supporting the testicular dysgenesis syndrome hypothesis. Conservative surgery and active surveillance are alternative safe options, but require monitoring of testicular failure and recurrence.